Gut microbiome and peritoneal inflammation: a new perspective on peritoneal dialysis-associated peritonitis - Penghao Xu; Mengjie Zhang; Shiyan Cui; Lingling Wang; Yanni Li; Yuchen Li; Chen Jiang (Renal Failure)
Background Gut microbiome disorders and intestinal barrier damage were found in peritonitis. However, the relationship between the gut microbiome and peritoneal dialysis-associated peritonitis (PDAP) remains unknown. This study aimed to investigate the role of the gut microbiome in PDAP and explore its correlation with intra-abdominal inflammation.Methods We used a two-fold strategy to investigate the causal relationship between the gut microbiome and PDAP. First, a Mendelian randomization (MR) study was conducted using summarized statistics from genome-wide association studies (GWAS) of the gut microbiome and peritonitis. Additionally, a case-control study with 24 patients from the peritoneal dialysis (PD) and PDAP groups were conducted to validate the role of candidate bacteria in peritonitis, using 16S rRNA sequencing to capture their gut microbiomes.Results We screened four protective and one risky bacteria for peritonitis using MR analysis. The results of MR analysis were validated in the case-control study. We observed a shift in the co-occurrence pattern from the PD group to the PDAP group, suggesting potential destabilization of the gut bacterial network in the PDAP group. Furthermore, analysis of 17 protective and three risky bacteria revealed differential bacteria through LefSe and random forest analyses. Among these, we observed a significant negative correlation between Faecalibacterium, Coprococcus, Dorea, Anaerostipes, and Lachnospira and interleukin-6 levels.Conclusion Gut microbiome dysbiosis in peritoneal dialysis patients is a significant contributing factor to PDAP, with alterations in microbial abundance showing a strong correlation with the severity of intraperitoneal inflammation.